Investigation of total phenolic content and antioxidant activities of Azadirachta indica roots - Md. Delowar Hossain; Md. Shahid Sarwar; Syed Masudur Rahman Dewan; Md. Shohel Hossain; A. F. M. Shahid-; Mohammad Safiqul Islam (Mashhad University of Medical Sciences, 2014)
Objective: The present study was an attempt to study total phenolic content and antioxidant property of the crude ethanolic extract of the roots of Azadirachta indica (A. indica). Materials and Methods: To evaluate the antioxidant properties of the crude extract, some complementary test systems, namely DPPH free radical scavenging assay, reducing power assay, and ferrous ion chelating ability and determination of total phenolic content were conducted. Results: In DPPH free radical scavenging test, IC50 value of the crude extract was found to be fairly significant (13.81±0.06 μg/ml) while compared with that of the reference standards, ascorbic acid and BHA (2.12±0.02 and 4.87±0.05 μg/ml, respectively). In reducing power assay, the maximum absorbance for the extract was found to be 1.523 ±0.026 at 100 μg/ml compared with standard ascorbic acid and BHA (2.811±0.013 μg/ml and 2.031±0.019 μg/ml, respectively). The IC50 value of the extract as percentage of Fe++ ion chelating ability was determined as 19.01±0.024 μg/ml where EDTA showed 8.87±0.035 μg/ml. The total phenolic amount was also calculated quite high in the extract (238.81±0.98 mg/g of gallic acid equivalent). Conclusion: The assays showed the presence of significant antioxidant properties of the crude sample, which would justify its traditional use. However, it would be very interesting to investigate the possible causes and their mechanisms responsible for the antioxidant property of the plant A. indica.